Dentition development and budding morphogenesis - Peterková, R; Peterka, M; Viriot, L; Lesot, H (Journal of craniofacial genetics and developmental biology, 2000)
The development of functional teeth in the mouse has been widely used as a model to study general mechanisms of organogenesis. Compared with other mammals, in which three incisors, one canine, four premolars, and three molars may occur even in each dental quadrant, the mouse functional dentition is strongly reduced. It comprises only one incisor separated from three molars by a toothless gap diastema at the location of the missing teeth. However, mouse embryos also develop transient vestigial dental primordia between the incisor and molar germs in both the upper and lower jaws. These rudimental structures regress, and epithelial apoptosis is involved in this process. The existence of the vestigial dental structures allowed a better assessment of the periodicity in the mouse dentition, which extends opportunities for the interpretation of molecular data on tooth development. We compared the dentition development with tentative models of budding morphogenesis in other epithelial appendages lungs and feathers. We suggested how developmental control by signaling molecules, including bone morphogenetic protein (Bmp), sonic hedgehog (Shh), and fibroblast growth factor (Fgf), can be similarly involved during budding morphogenesis of dentition and other epithelial appendages. We propose that epithelial apoptosis plays an important role in achieving specific features of dentition, whose development involves both budding and its more complex variant branching. The failure of segregation of the originating buds supports the participation of the concrescence of several tooth primordia in the evolutionary differentiation of mammalian teeth.
Keywords: Animals; Signal Transduction; epitel; Epithelium; Cell Differentiation; Morphogenesis; morfogeneze; buněčná diferenciace; zvířata; Mice; zuby; signální transdukce; Tooth; myši